Paleomagnetism for Geologists - Park, John (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1983)
Summary Paleomagnetism is a useful tool for geologists. It gives simple data on remanent and induced magnetizations in rocks, which may help to distinguish or characterize them, determine their structural relationships with respect to other units, unravel their geological histories and infer their latitude of formation. Magnetic parameters separately, together or combined with density may also be used to identify and map various primary and secondary geological processes. In view of the utility of paleomagnetic methods, geologists and paleomagnetists should become routinely involved in joint projects.